Dançando para Deus: música e dança a serviço da fé nas cristotecas católicas - Sena, Luzia Maria de Oliveira (2011)
The subject of this research is to analyze the catholic parties called cristotecas , promoted since 2003 by the group Movimento Eclesial Aliança de Misericórdia , in São Paulo city. It aims to know the origin, the objectives, the organizative structure of the cristotecas , as well as the intents of the young people who take part of them and the influence of these parties over the youth. The cristotecas are analysed from the point of view of their inclusion in a wider context, configured by social and cultural changes the modern contemporary societies are passing over, whose transformations fall over the religious field and rouse new forms of organization and religious expressions. The focus of the investigation aims to verify how the music and the dance both coexisting along the human existence with religious purposes are used by the cristoteca not only for youth‟s leisure and entertainment, but specially as an strategy of evangelization: to attract the young people, to provide them a religious experience and an encounter with God, and to bring them to the Catholic Church communitarian convivial